2018
DOI: 10.21037/jtd.2018.04.46
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level analysis of bacteria isolated from inpatients in respiratory departments in China

Abstract: In China, the predominant bacterial pathogens in the respiratory ward were and non-fermentative bacteria. High prevalence of ESBL-EC and ESBL-KP isolated from lower respiratory tract (LRT) was revealed in primary hospitals and pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…But at present, the rate of blood culture in Chinese patients with LRIs was not high. A multicenter study from China showed that blood culture isolates accounted for only 5.3% of all specimen types [1][2]. For LRIs, should we do blood culture or sputum culture?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But at present, the rate of blood culture in Chinese patients with LRIs was not high. A multicenter study from China showed that blood culture isolates accounted for only 5.3% of all specimen types [1][2]. For LRIs, should we do blood culture or sputum culture?…”
Section: Discussionmentioning
confidence: 99%
“…Lower respiratory tract infections (LRIs) were the most common infectious disease of respiratory tract [1][2]. Irrational use of antibiotics would delay the patient's condition and cause serious bacterial resistance [1][2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower respiratory tract infections (LRIs) were the most common infectious disease of respiratory tract. [1][2] Pneumonia was the second most common infection in hospitalized patients, and was highly correlated with morbidity and mortality. [3] Irrational use of antibiotics would delay the patient's condition and cause serious bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Irrational use of antibiotics would delay the patient's condition and cause serious bacterial resistance. [1][2] According to the data from China Antimicrobial Resistance Surveillance System (CARSS) in 2015, the major specimens type from inpatients in respiratory departments in China were sputum (81.6%, 41,131/50,417). [1][2] Due to the convenience of specimens collection, sputum had always been the most common type of specimens in clinical microbiology laboratories in China.…”
Section: Introductionmentioning
confidence: 99%